Impact of Net Foreign, Return, Rupiah Exchange Rate on Capital Market Liquidity in Indonesia - Evi Aisah Tresnaningsih; Etty Puji Lestari; Said Kelana Asnawi (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
Trading volume (liquidity) is one of the important indicator for investors to monitor the movement of stock prices on the Indonesian stock exchange (IDX). Investors are attracted to stocks that provide high returns, have a tendency to rise in price, and have high liquidity. One of the factors that affect liquidity is investment in foreign stocks, where foreign investors are still the catalyst for stock movements in the Indonesian Capital Market. This study uses time-series data obtained from all listed stocks as a component of the calculation of the Composite Stock Price Index (IHSG) based on the average daily trading transaction value during the 2017-2019 period. This study consists of four variables where one dependent variable is liquidity with value proxy and three independent variables which are net foreign, return, and the exchange rate of the rupiah against the US dollar. These variables were then analyzed qualitatively in the form of descriptive statistics and multiple linear regression analysis. The result of the research shows that net foreign exchange increases trading volume. Based on the results of the descriptive analysis for the period 2017-2019, foreign investors still dominate the stock market in Indonesia. The dominance of foreign stocks can be interpreted as high investor confidence in the ability of the Indonesian government and the positive perception of foreign investors in the Indonesian capital market which is still very profitable for their investment. The opposite result is in the variable return where liquidity increases in a bearish market. In contrast, the depreciation of the rupiah against the dollar increased trading volume, although not significantly.